2015
DOI: 10.1007/s12094-015-1351-6
|View full text |Cite
|
Sign up to set email alerts
|

Response to chemotherapy estimates by FDG PET is an important prognostic factor in patients with Ewing sarcoma

Abstract: (18)F-FDG PET demonstrates high diagnostic accuracy for response to initial chemotherapy in patients with ES and it correlates with outcome. The role of FDG PET in predicting response and outcome should be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 30 publications
3
26
1
Order By: Relevance
“…The strength of this study was the homogeneity of treatment, including the duration of neoadjuvant chemotherapy, the surgical team and pathological assessment, all important determinants of EFS that could be confounding factors in assessing the predictive value of FDG PET. The concordance between a good histological response (>90 % tumour necrosis in OS patients and Picci II/III necrosis in EWS patients) and SUV1 (<6) in this study was very robust, confirming the findings in smaller series [15, 16, 32, 33], and is in contrast with the findings of a study performed in America [31]. Differences in patient characteristics (age), treatment and histological examination assessment could explain these conflicting results.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The strength of this study was the homogeneity of treatment, including the duration of neoadjuvant chemotherapy, the surgical team and pathological assessment, all important determinants of EFS that could be confounding factors in assessing the predictive value of FDG PET. The concordance between a good histological response (>90 % tumour necrosis in OS patients and Picci II/III necrosis in EWS patients) and SUV1 (<6) in this study was very robust, confirming the findings in smaller series [15, 16, 32, 33], and is in contrast with the findings of a study performed in America [31]. Differences in patient characteristics (age), treatment and histological examination assessment could explain these conflicting results.…”
Section: Discussionsupporting
confidence: 88%
“…SUV2 seems exclusively useful in EWS patients. In our study SUV2 was able to predict histological response, as shown in a paediatric series [32], and might be used for example by surgeons to plan a local treatment approach. Furthermore, a good metabolic response was associated with best survival in EWS patients (80 % 3-year EFS in patients with a reduction in SUV2 of ≥55 %, in contrast to 20 % in patients with a poor metabolic response).…”
Section: Discussionmentioning
confidence: 70%
“…A surrogate metric to determine whether treatment intensification is warranted in patients undergoing RT is needed. Many studies demonstrate tumors with minimal metabolic changes on [ 18 F]fluorodeoxyglucose positron emission tomography ( 18 F-FDG PET) following neo-adjuvant therapy are associated with a higher risk of progression (21-23). None of these reports discuss the association of local tumor control with 18 F-FDG PET, so it is unclear whether 18 F-FDG PET has a role in determining high-risk RT cases.…”
Section: Discussionmentioning
confidence: 99%
“…While mutations in the STAG2 , CDKN2A , and TP53 genes can be found in about 20% of Ewing's sarcoma cases, their prognostic significance remains controversial . Moreover, the prognostic and predictive utility of 18F‐fluorodeoxyglucose positron emission tomography in Ewing's sarcoma has been reported.…”
Section: Research Directions In Ewing's Sarcomamentioning
confidence: 99%